(3GdSdhc GdJfXjei Hjf GdfXQjI hGdJWHjb (B/s - (3eMeO GSeGYjd, HdGds ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2005)
(3eaGgje GSGSjI, XZhW GdYed, OGaY GdYed, GdGOQGc, Gdbje, GYOGO hJfejI GdbjGOGJ, GdGJUGds
(3GdeQGLY U(B.385s
Keywords: (3GdGJUGds; (3GdJfXje GdEOGQjs; (3GdSdhc GdEOGQjs; (3GdYdGbGJ GdEfSGfjIs